Estimating fetal dose from tube current‐modulated (TCM) and fixed tube current (FTC) abdominal/pelvis CT examinations. Issue 6 (24th April 2019) - Hardy, Anthony J.; Angel, Erin; Bostani, Maryam; Cagnon, Chris; McNitt‐Gray, Michael
Abstract : Purpose: The purpose of this work was to estimate scanner‐independent CTDIvol ‐to‐fetal‐dose coefficients for tube current‐modulated (TCM) and fixed tube current (FTC) computed tomography (CT) examinations of pregnant patients of various gestational ages undergoing abdominal/pelvic CT examinations. Methods: For 24 pregnant patients of gestational age from <5 to 36 weeks who underwent clinically indicated CT examinations, voxelized models of maternal and fetal (or embryo) anatomy were created from abdominal/pelvic image data. Absolute fetal dose ( D fetus ) was estimated using Monte Carlo (MC) simulations of helical scans covering the abdomen and pelvis for TCM and FTC scans. Estimated TCM schemes were generated for each patient model using a validated method that accounts for patient attenuation and scanner output limits for one scanner model and were incorporated into MC simulations. FTC scans were also simulated for each patient model with multidetector row CT scanners from four manufacturers. Normalized fetal dose estimates, nD fetus, was obtained by dividing D fetus from the MC simulations by CTDIvol . Patient size was described using water equivalent diameter ( D w ) measured at the three‐dimensional geometric centroid of the fetus. Fetal depth (DEf ) was measured from the anterior skin surface to the anterior part of the fetus. nD fetus and D w were correlated using an exponential model to develop equations for fetal dose conversion coefficients for TCM and FTC abdominal/pelvic CT examinations. Additionally, bivariate linear regression was performed to analyze the correlation of nD fetus with D w and fetal depth ( DE f ). For one scanner model, nD fetus from TCM was compared to FTC and the size‐specific dose estimate (SSDE) conversion coefficients ( f ‐factors) from American Association of Physicists in Medicine (AAPM) Report 204. nD fetus from FTC simulations was averaged across all scanners for each patient ( n D fetus ¯ ) . n D fetus ¯ was then compared with SSDE f‐ factors and correlated with D w using an exponential model and with D w and DE f using a bivariate linear model. Results: For TCM, the coefficient of determination ( R 2 ) of nD fetus and D w was observed to be 0.73 using an exponential model. Using the bivariate linear model with D w and DE f, an R 2 of 0.78 was observed. For the TCM technology modeled, TCM yielded nD fetus values that were on average 6% and 17% higher relative to FTC and SSDE f ‐factors, respectively. For FTC, the R 2 of n D fetus ¯ with respect to D w was observed to be 0.64 using an exponential model. Using the bivariate linear model, an R 2 of 0.75 was observed for n D fetus ¯ with respect to D w and DE f . A mean difference of 0.4% was observed between n D fetus ¯ and SSDE f ‐factors. Conclusion: Good correlations were observed for nD fetus from TCM and FTC scans using either an exponential model with D w or a bivariate linear model with both D w and DE f . These results indicate that fetal dose from abdomen/pelvis CT examinations of pregnant patients of various gestational ages may be reasonably estimated with models that include (a) scanner‐reported CTDIvol and (b) D w as a patient size metric, in addition to (c) DE f if available. These results also suggest that SSDE f ‐factors may provide a reasonable (within ±25%) estimate of nD fetus for TCM and FTC abdomen/pelvis CT exams. Abstract :